Euro Area : Report on Observance of Standards and Codes Assessment of Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies-Monetary Policy and Payment System Oversight, and the CPSS Core Principles for Systemically Important Payment Systems (Target and the EURO1 Payment Systems). (IMF Staff Country Reports; Country Report ;, 2001)
The Euro system maintains a high level of transparency in all aspects of operations, demonstrating a strong institutional commitment to openness and a high degree of observance of the code. Greater consistency in the disclosure practices of individual National Central Banks (NCBs) will ensure that the conduct of monetary policy, payment system oversight, and the development of financial markets proceed in a uniform basis. Executive Directors suggests that the European Central Bank (ECB) review its current practice of selective and informal public consultation on payment issues.